Анализ залоговых рисков и выработка рекомендаций по их минимизации (Путеводитель предпринимателя)
In given article process of the analysis of mortgaging risks and development of recommendations about their minimisation is in detail resulted. Namely measures on minimisation of risks are presented, the managerial process information field is presented by credit risk.